Association of the humoral immune response with the inflammatory profile in Plasmodium vivax infections in pregnant women. - Rodrigo Medeiros de Souza; Maria Inês Dos Santos; Laura Cordeiro Gomes; Bruna Beatriz Pedroza de Melo; Erika Paula Machado Separovic; Oscar Murillo; Gerhard Wunderlich; Taane Gregory Clark; Susana Campino; Sabrina Epiphanio; Claudio Romero Farias Marinho; Jamille Gregório Dombrowski (Public Library of Science (PLoS), 2024)
Background Plasmodium vivax infection, when it occurs during pregnancy, has often been associated with serious adverse pregnancy outcomes. However, immunological alterations in pregnancy and their consequences have been little explored. We characterized the humoral immune response in pregnant women exposed to malaria by P. vivax antigens and its association with the maternal inflammatory profile and poor pregnancy outcomes. Methods An observational cohort study in the Brazilian Amazon was conducted between 2013 and 2015. After applying exclusion criteria, 242 mother-child pairs were included in the analysis. Data on maternal infection, gestational outcomes, and inflammatory factors were evaluated in the maternal peripheral plasma. In samples from the first infection, the presence of total IgG and its subclasses in plasma against PvMSP119 protein were also quantified. Results Previous exposure to malaria, observed by anti-total IgG antibodies to the PvMSP119 antigen, increased the inflammatory response to infection when the pregnant woman had malaria during pregnancy. IL-6 and IL-10 levels were positively correlated with parasitemia and with total IgG levels; but they were negatively correlated with the gestational age at delivery from Pv-infected woman. In multivariate linear regression analyses, IgG 1, 2 and 4 was negatively and positively associated with cytokines IL-6 and IL-10, respectively, in P. vivax-infection. Conclusions An association between the humoral immune response and the peripheral inflammatory cytokine profile with the adverse outcomes in malaria in pregnancy by P. vivax was observed. Previous exposure to the parasite can influence the IL-6 and IL-10 response, which is associated with increased parasitemia, reduced maternal weight gain and premature delivery.